2015
DOI: 10.1620/tjem.237.297
|View full text |Cite
|
Sign up to set email alerts
|

Eczema and Asthma Symptoms among Schoolchildren in Coastal and Inland Areas after the 2011 Great East Japan Earthquake: The ToMMo Child Health Study

Abstract: After the Great East Japan Earthquake of 2011, there has been a concern about health problems among children. Therefore, we investigated the prevalence of wheeze and eczema symptoms and associated factors among children in areas primarily affected by the disaster. From 2012 to 2014, we distributed the parent-administered questionnaire to 25,198 children in all 233 public schools in the 13 municipalities of Miyagi Prefecture in northeast Japan. A total of 7,155 responses (mean age 10.5 ± 2.2 years) were receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 26 publications
2
24
1
1
Order By: Relevance
“…One explanation for our findings is that even though the prevalence of eczema symptoms are showed to be higher among younger children in previous studies, the severity of these symptoms have been found to increase over time since eczema became exacerbated with increased age . Another possible explanation could lie in recent studies’ findings that higher prevalence of ES was found among children who had experienced a natural disaster . The majority of older children in the present study might have experienced the 2004 tsunami in Aceh in a very early age, whereas younger children did not experience it.…”
Section: Discussioncontrasting
confidence: 61%
“…One explanation for our findings is that even though the prevalence of eczema symptoms are showed to be higher among younger children in previous studies, the severity of these symptoms have been found to increase over time since eczema became exacerbated with increased age . Another possible explanation could lie in recent studies’ findings that higher prevalence of ES was found among children who had experienced a natural disaster . The majority of older children in the present study might have experienced the 2004 tsunami in Aceh in a very early age, whereas younger children did not experience it.…”
Section: Discussioncontrasting
confidence: 61%
“…Furthermore, we did not include school-aged children, whose developmental stage might be different from that of preschool children, in our survey. In a previous study, Miyashita et al 24 reported that the prevalence of eczema symptoms among children in the second and eighth grades after the Great East Japan Earthquake was higher compared with the average in Japan, and experiencing the ‘tsunami’ was significantly associated with a high prevalence of eczema. Our results might support the possibility that children overall who experience a mega disaster could experience negative health effects.…”
Section: Discussionmentioning
confidence: 98%
“…likely to worsen due to air pollution or post-traumatic stress disorder. [6][7][8] Therefore, anaphylaxis is likely to occur during disasters. In this survey, almost all patients prescribed adrenaline carried the medication, which was also common in patients investigated in another study.…”
Section: Discussionmentioning
confidence: 99%